Strategi Peningkatan Kesadaran Masyarakat Terhadap Rokok Ilegal di Kelurahan Bandungan Kecamatan Bandungan Kabupaten Semarang - Syaiful Amin; Deswal Waskito; Nandita Novia Anggraini; Edi Santosa (Jurnal Bina Desa, 2026)
Illegal cigarettes are a serious problem in Indonesia that has an impact on the health, economy, and social of the community. Illegal cigarettes cause the state to suffer losses of up to trillions of rupiah due to the loss of excise revenue. One of the efforts made by the Directorate General of Customs and Excise to suppress the circulation of illegal cigarettes is through the Illegal Cigarette Strike program. This service aims to increase public awareness of the dangers and negative impacts of illegal cigarettes through the implementation of the Illegal Cigarette Strike program in Bandungan Village. The method of implementing this program consists of four main stages, namely campaigns, socialization, education, and advertising creation. The program was carried out from February 16 to March 6, 2025 by the UNNES GIAT 11 team in collaboration with village officials. The results of the activity show an increase in public understanding of the characteristics of illegal cigarettes and their impact on the state. This program is a strategic step in reducing the circulation of illegal cigarettes in Indonesia through increasing awareness and active participation of the public in efforts to eradicate illegal cigarettes.